Integral and transformative engineering coursework in formative research for undergraduate curricula - Mugruza Vassallo, Carlos (2016)
At several private Peruvian universities, formative research was not included in the curricula design. Here the problem to solve was the small number of undergraduate dissertations in Engineering. First, the coursework design and tutoring were reviewed and reformulated. The former proposal was based on the triangle of Peñaloza Ramella [1], in this study, this view was extended to a double triangle. The proposed extension uses an inverted triangle in order to compensate for the insufficient preparation in high school. Second, problems were identified comparing current outcomes against the desired undergraduate dissertations. The design used a mix of the transformative research ideas at US education institutions [2] and the triangle's formulation of Peñaloza-Ramella [1], where the first triangle is to assure student preparation for different ways of formative research and the second one is to adapt the coursework to the original triangle to get more specific results each semester. Furthermore, several aspects in the use of resources were promoted (e.g. use of IEEE Xplore databases). In the first year, results have shown (1) acceptance by former students (before academic semester 2014-2) of these changes, generating 12 dissertations, (2) a change in few courses in formative research clearly enhanced at semesters II, III and VII, (3) an increase in the number of undergraduate dissertations during coursework, (4) first works accepted and presented in a Peruvian Student Competition Congress (5) all alumni with professional degrees have completed their undergraduate dissertation. Finally, in the next four years, a new generation of students is going to emerge with a significant improvement of their quality and their reasoning skills.